IMPLEMENTATION OF SPRING ANALOGY METHOD BASED DYNAMIC GRID FOR FLUID STRUCTURE INTERACTION PROBLEM - Muhammad, Diksan
The dynamic grid is one of the important aspects in computational fluid dynamics to solve moving boundary problem. The moving boundary describes the structural movement or deformation either due to fluid pressure distribution or due to prescribed movement of the boundary on fluid domain. This moving boundary problem is often found in fluid structure interaction (FSI) where the dynamic of structure and fluid are affecting each other. FSI is utilized to predict the change of fluid behavior as well as change of pressure distribution during a structural movement. When the boundary movement is introduced to the initial mesh, the mesh is updated due to the boundary movement. Smoothing process with mesh deformation is required to improve the updated mesh quality because sometimes after the boundary movement, poor mesh quality will appear. Mesh deformation is chosen due to its ability to move the mesh without changing its connectivity. During the structural motion, edges of mesh is modelled as a linear spring called spring analogy method and additional spring inside a cell will act like a reinforcement to avoid cell inversion problem. The new mesh is obtained after the equilibrium state of the spring reached. The mesh quality of orthogonality is monitored to check the mesh quality after structural movement. However, poor element quality might still appear after structural movement. So, the mesh angle above 120° is treated with edge switching to further improve the mesh quality with consequence of small changes in connectivity. Data structure required by OpenFOAM should be listed so that the mesh and its motion can be simulated in OpenFOAM. The methods are tested by a case of rotating box with 65° angle where cell inversion problem occurs in spring method without reinforcement. The simplest approach which is spring method without reinforcement is applied to a simple boundary problem. A defined translational and rotational movement of a box in a waterflow. It is observed that the spring method with reinforcement gives better mesh quality compared to the without reinforcement spring. But the edge switching technique does not show the mesh quality improvement. The result also shows that the data structure can be read by OpenFOAM after data structure conversion.